Perception of the signs and symptoms of temporomandibular disorder in females by using the ProTMDMulti protocol and the visual analog scale before and after acupuncture treatment. Issue 2 (3rd March 2016) - Branco, Carolina Assaf; Fonseca, Rodrigo Borges; Borges, Renata Filgueira; Venezian, Giovana Cherubini; Magri, Laís Valencise; Mazzetto, Marcelo Oliveira
Abstract : Objective: To evaluate the perceptions of patients with TMD in relation to the signs and symptoms before and after acupuncture treatment, according to the ProTMDMulti and the VAS. Method: 68 patients were divided into groups: muscle TMD treated with acupuncture at local points (MUS-LP), muscle TMD with acupuncture at distant points (MUS-DP), joint and muscle treated with LP (JOI-LP) and joint and muscle treated with DP (JOI-DP). The evaluations were performed at four times: initial, control, final and follow-up. Results: The best results were seen in the JOI-LP and the MUS-DP groups, in which the perceptions of the signs and symptoms were statistically lower in the final assessment than in the initial (P<0.05). In all groups, the final and the follow-up evaluations were similar. Conclusions: For TMDs with joint components, the best acupuncture treatment involves local points and for the TMDs with muscle components, points at a distance.